2008
DOI: 10.1002/pmic.200800061
|View full text |Cite
|
Sign up to set email alerts
|

Structural features and the persistence of acquired proteins

Abstract: ORFan genes can constitute a large fraction of a bacterial genome, but due to their lack of homologs, their functions have remained largely unexplored. To determine if particular features of ORFan-encoded proteins promote their presence in a genome, we analyzed properties of ORFans that originated over a broad evolutionary timescale. We also compared ORFan genes to another class of acquired genes (HOPs), which have homologs in other bacteria. A total of 54 ORFan and HOP genes selected from different phylogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…Unlike the ORFan proteins, which are unique to a given species or strains and are subject to rapid gene loss (Siew and Fischer 2003;Lerat et al 2005), these SPs proteins are distinctive characteristics of all or most species/strains from a given clade, indicating that they are important for these groups (Graham et al 2000;Fang et al 2005;Fang et al 2008;Narra et al 2008;Dutilh et al 2008b;Gao et al 2009). Although the mechanism responsible for the evolution of genes for these proteins is unclear (Dutilh et al 2008b;Kuo and Ochman 2009), their presence in specific clades indicates that their genes first evolved or were introduced in a common ancestor and were retained by its descendents.…”
Section: (B)mentioning
confidence: 97%
“…Unlike the ORFan proteins, which are unique to a given species or strains and are subject to rapid gene loss (Siew and Fischer 2003;Lerat et al 2005), these SPs proteins are distinctive characteristics of all or most species/strains from a given clade, indicating that they are important for these groups (Graham et al 2000;Fang et al 2005;Fang et al 2008;Narra et al 2008;Dutilh et al 2008b;Gao et al 2009). Although the mechanism responsible for the evolution of genes for these proteins is unclear (Dutilh et al 2008b;Kuo and Ochman 2009), their presence in specific clades indicates that their genes first evolved or were introduced in a common ancestor and were retained by its descendents.…”
Section: (B)mentioning
confidence: 97%
“…A vast number of lineage-specific proteins unique to certain species, strain or even genome, which are also called ''ORFans'', are introduced recently during speciation or strain divergence (Daubin and Ochman 2004). Studies have shown that these proteins present at the tips of the phylogeny evolve fast and are subject to loss if not conferring advantages to the host (Narra et al 2008;Kuo and Ochman 2009). However, if the lineage-specific proteins originate deep within a clade and are retained by all the descendents from the progenitor, they are confined to the monophyletic group (Gao et al 2006;Dutilh et al 2008;Gupta and Gao 2010;Gupta and Mathews 2010).…”
Section: Conserved Indels and Lineage-specific Proteins As Novel Toolmentioning
confidence: 97%
“…The sum of both core and noncore genes from different strains of a given species is now referred to as the ''pan-genome'' (Tettelin et al 2008). The non-core genes are postulated to contribute to functions such as niche adaptation, antibiotic resistance and the ability to colonize new hosts (Kuo and Ochman 2009;Narra et al 2008;Coleman and Chisholm 2010;Tettelin et al 2008). Based upon their branching in phylogenetic trees, genomic arrangement and uniquely shared genes/proteins (Touchon et al 2009;Liu et al 1999;Gupta, unpublished results), different strains of some species can be divided into a number of distinct clades.…”
Section: Current Issues In Microbial Systematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the orphan open reading frame (ORFan) proteins that are specific for particular species or strains and are subject to rapid loss (64,175,265), many proteins of unknown (or even known) functions are unique and distinctive, characteristic of various species from monophyletic clades of different phylogenetic depths (74,98,100,118,130,274). The presence of these proteins in a conserved state in all or most species and strains from these clades, but nowhere else, suggests that the genes for these proteins first evolved in a common ancestor of these clades, followed by their retention by various descendants (74,80,98,100,210). Thus, these proteins represent CSPs that are distinctive characteristics of particular lineages, and they provide useful molecular markers for defining or distinguishing those groups from other bacteria (118).…”
Section: Usefulness Of Conserved Signature Indels and Signature Protementioning
confidence: 99%